Anaerobic mercury methylators inhabit sinking particles of oxic water columns. (1st February 2023) - Capo, Eric; Cosio, Claudia; Gascón Díez, Elena; Loizeau, Jean-Luc; Mendes, Elsa; Adatte, Thierry; Franzenburg, Sören; Bravo, Andrea G.
Highlights: Anaerobic mercury methylators are present in sinking particles of temperate-lake oxic water columns. Firmicutes are predominant mercury methylators in sinking particles from temperate-lake oxic water columns. Desulfobacterota as abundant mercury methylators in both sinking particles from oxic water columns and anoxic sediments. Abstract: Increased concentration of mercury, particularly methylmercury, in the environment is a worldwide concern because of its toxicity in severely exposed humans. Although the formation of methylmercury in oxic water columns has been previously suggested, there is no evidence of the presence of microorganisms able to perform this process, using the hgcAB gene pair ( hgc + microorganisms), in such environments. Here we show the prevalence of hgc + microorganisms in sinking particles of the oxic water column of Lake Geneva (Switzerland and France) and its anoxic bottom sediments. Compared to anoxic sediments, sinking particles found in oxic waters exhibited relatively high proportion of hgc + genes taxonomically assigned to Firmicutes. In contrast hgc + members from Nitrospirae, Chloroflexota and PVC superphylum were prevalent in anoxic sediment while hgc + Desulfobacterota were found in both environments. Altogether, the description of the diversity of putative mercury methylators in the oxic water column expand our understanding on MeHg formation in aquatic environments and at a global scale. Graphical abstract: Schematic view of microbial players in mercury methylation in Lake Geneva. Image, graphical abstract